Diplomatic Associations and Exchange Rates : A Study on Russia-Ukraine War - Kundu, Sayantan; Banerjee, Aditya (Indian Journal of Finance, 2023)
Purpose : This paper aimed to analyze the impact of the Russia-Ukraine war on the currencies of two major groups of nations based on their diplomatic association with Russia, viz., those against invasion and the non-aligned group. Methodology : The methodology adopted in this paper could be divided into two parts. In the first part, the event study method was used to analyze the aggregated impact of war on the currencies of the two groups of nations. In the second part, a dynamic conditional correlation–generalized autoregressive conditional heteroskedastic model (DCC-GARCH) was used to analyze the dynamic correlation between the two groups of currencies in aggregate. Findings : From the first part of the analysis, it was found that the Russian ruble declined for both groups after the initial economic sanctions, but the recovery afterward was more robust against the currencies of the non-aligned group. The second part of the analysis revealed a significant increase in the time-varying dynamic conditional correlation between the returns of the two groups after the war, indicating a contagion. Practical Implications : Managers are recommended to be cautious of the impact of the increased interrelation of exchange rates among the two diplomatic groups on international business transactions. Policymakers are recommended to consider the fact that economic sanctions not uniformly supported by all major nations cannot have their intended impact. Originality : This paper is the first to examine the impact of the Russia-Ukraine war on foreign exchange rates from the perspective of diplomatic associations of nations.